Impacts of rapid urbanization on ecosystem services under different scenarios – A case study in Dianchi Lake Basin, China. (November 2021) - Wang, Ruibo; Bai, Yang; Alatalo, Juha M.; Yang, Zhangqian; Yang, Zongbao; Yang, Wei; Guo, Guimei
Graphical abstract: Highlights: Driving factors and mechanisms underlying urbanization in DLB were clarified. Three urbanization scenarios land uses maps of DLB in 2035 were simulated. ESs in 2035 under three urbanization scenarios were evaluated and tradeoffed. An optimized urbanization path and land use pattern were proposed. Ecological Red Line, Ecological Isolation Strips, economic and intensive use of land should be targeted. Abstract: Dianchi Lake Basin (DLB) is a typical and representative type of urbanization model based on the plateau lake ecosystem, with scarce land resources, deficient water resources, and a fragile ecological environment, in parallel with large-scale and rapid urbanization. To increase ecological security and maintain ecosystem services (ESs), it is essential to analyze the paths and processes for implementing sustainable urbanization. Using combined CLUE-S-Markov-InVEST modeling, the study simulated ESs changes and distribution in DLB under a natural increase scenario (NIS), an urban plan scenario (UPS), and an ecological protection scenario (EPS). EPS proved to be the best-optimized urbanization path and land use pattern that can meet land use demand for urbanization, but also maintain (or even improve) regional ESs levels. The major driving mechanisms underlying urbanization effects on ESs were found to be selection of urbanization path, scale control and layout of construction land, demarcation and implementation of ecological red line and ecological protection areas. The results indicate that DLB should follow the EPS urbanization path, an ecological red line should be reasonably delineated and observed, and ecological isolation strips should be established at appropriate locations. Additionally, the scale of construction land should be strictly controlled, constructed land should be used more intensively, and the utilization efficiency of construction land should be improved.